Social Relations Network in Building Civilization An Analysis of Its Significance (Rangkaian Perhubungan Sosial Untuk Membina Ketamadnan Satu Analisis Kepentingannya) - Berghout, Abdelaziz; Berghout, Zakia (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract This paper introduces the concept of social relations network as an important element in the process of building a civilisation. In general terms, any human society embarking on a civilizing process needs, among other things, four integral ingredients namely people, ideas, objects and social relations network. The realm of persons provides the human capital and talents. The realm of ideas offers worldviews, ideologies, philosophies, visions, concepts, values, and perspectives. Whereas, the realm of objects makes available things, tools, products, know-how, instruments and the necessary needs of a society. However, these three important realms remain mere isolated elements in the absence of the fourth realm that synthesises and articulates them in the form of a civilising project leading to the development of society. This fourth realm is but the social relations network that integrates and puts persons, ideas and objects together in a bid to build a civilisation. This paper uses textual analysis to examine the notion of social relations network and its function in the process of building civilisation. It draws a special attention to the views of Malik Bennabi and his understanding of and approach to the notion of social relations network and how it works in making a civilisation. Keywords: Social Relations Network, Ideas, Persons, Objects, Civilization. Abstrak Kajian ini memperkenalkan konsep rangkaian hubungan sosial sebagai satu elemen penting dalam proses membina ketamadunan. Secara amnya, masyarakat manusia memulakan proses ketamadunan memerlukan, empat bahan penting iaitu orang, idea-idea, objek dan rangkaian hubungan sosial. Orang menyediakan modal insan dan bakat. Idea menawarkan pandangan dunia, ideologi, falsafah, visi, konsep, nilai dan perspektif. Manakala, objek menyediakan, alat, produk, pengetahuan, alat dan keperluan yang diperlukan dalam sesebuah masyarakat. Walau bagaimanapun, ketiga-tiga bahan ini kekal terpencil jika tiada bahan keempat, yang mensintesisnya dalam bentuk ketamadunan untuk membangunkan masyarakat. Bahan keempat iatu rangkaian hubungan social, yang mengintegrasikan dan meletakkan orang, idea-idea dan objek bersama untuk membina ketamadunan. Kajian ini menggunakan analisis teks untuk memeriksa tanggapan rangkaian hubungan sosial dan fungsinya dalam proses pembinaan ketamadunan. Ia perhatikan secara khusunya kepada pandangan, pemahaman dan pendekatan Malik Bennabi kepada konsep rangkaian hubungan sosial dan bagaimana ia berfungsi dalam membina ketamadunan. Kata Kunci: Rangkaian Perhubungan Sosial, Idea-idea, Orang, Objek , Ketamadunan.